As influências da paisagem urbana em grupos funcionais e riqueza de aves - Aguiar, Albert Gallon de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Urbanized landscapes support classical macroecological patterns as specie-area relationship, abundance and biomass. Cities play an important role in the conservation of global biodiversity for those reasons. For birds, 20% of the total species occur in urban centers worldwide. Nonetheless, the growth urbanization process promotes profound effects on bird diversity, negative for non-urban species and positive for urban-tolerant. This study aimed to identify the scientific conclusions presented up to date on landscape effects on urban bird communities. We applied a systematic review, searching for scientific publications regarding bird ecology in urban environment from the landscape scale perspective. More than a thousand articles were found referring to birds in urban landscapes. However, just a tenth of them applied landscape metrics to understand the relationships between birds and urban landscapes. The single-scale approach was the option adopted by 65% of all publications. Most of the studies aimed a biodiversity conservation view of the urbanization process using bird communities in high-incoming areas. Developing countries are usually neglected by those studies, though currently they promote higher urban landscape transformation. Bird richness was the most common response variable, whereas just 20% of the studies considered functional data for species. Our conclusions in this work suggest that research efforts to understand urbanization effects on biodiversity have focused mostly at the patch scale only. Following the systematic review conclusions, we produced a second study to test the habitat amount hypothesis, verifying the relationship between avian community and urban areas, and to test whether patch or landscape scale would better explain the biodiversity. The results disagree with the habitat amount hypothesis and suggest that in urban landscapes the size of the native vegetation patches are more important than forest areas...

Paisagens urbanas suportam padrões macroecológicos, como as relações de espécie e área, abundância e biomassa. Por este motivo, as cidades têm um importante papel na preservação da biodiversidade global. Para o grupo das aves, 20% das espécies ocorrem em centros urbanos pelo mundo. No entanto, o processo de crescimento da urbanização promove profundos efeitos na diversidade de aves, podendo ser negativos para espécies não tolerantes a ambientes urbanos, ou positivos para aquelas que se adaptam bem. Esta dissertação é dividida em dois estudos, no primeiro buscou-se identificar as conclusões científicas atuais sobre os efeitos da paisagem em comunidades urbanas de aves. Para tanto, e por meio de uma análise sistemática da literatura, foram analisadas as publicações científicas tratando da ecologia de aves em ambientes urbanizados, na perspectiva da escala da paisagem. Mais de mil artigos foram encontrados referenciando aves em paisagens urbanas, e destes, apenas um décimo mediu esta relação de forma objetiva por meio de métricas de análise da paisagem. De todas as publicações revisadas, 65% fizeram análises da paisagem em apenas uma escala. A maior parte dos estudos teve como objetivo a conservação da biodiversidade no processo de urbanização em países ricos, os países em desenvolvimento, que mais transformam a paisagem pelo crescimento urbano, são geralmente negligenciados. A riqueza de espécies foi a variável resposta mais comum e 20% dos estudos utilizaram algum tipo de dado funcional sobre as espécies avaliadas. As conclusões deste estudo sugerem que as publicações buscando a compreensão dos efeitos da urbanização têm focado, em sua maioria, em estudos apenas na escala do fragmento. Seguindo as conclusões da análise sistemática da literatura, o segundo estudo desta dissertação testou a hipótese da quantidade de habitat remanescente (habitat amount...
Keywords: Ecologia urbana (Biologia); Ave; Conservação biológica; Urbanização; Florestas urbanas